Application of Classical Music Therapy and Finger-Holding Techniques on Patients Experiencing Post-Operative Pain in the Surgical Treatment Root - Hanny Irmaya; Intan Nabila; Waode Erty Hikma (GLOBAL HEALTH SCIENCE GROUP, 2024)
Postoperative pain is an experience of pain or unpleasantness caused by incision / cutting of tissue in certain parts. Classical Music Therapy Is a therapy that can calm, provide a sense of security and well-being, release joy and sadness, and reduce the pain and anxiety of patients after surgery, one of which is surgery. Finger grasping therapy is a therapy that can reduce pain sensation, pain stimulation due to respondent mediators, and pain. The application of finger grasping therapy and music therapy has advantages in handling the decrease in pain intensity for postoperative patients. The aim of this study was to analyze the application of classical music therapy and finger holding techniques in patients experiencing post-operative pain in the surgical treatment room. This type of research is a description with a case study approach model while the sample is 3 respondents who experience postoperative pain with moderate to severe intensity. Data was collected by measuring pain after the intervention. From the results of observations of pain intensity in all respondents, data was obtained that all respondents experienced pain after surgical operations on the stomach. After the application of classical music therapy and finger holding, the results were obtained, namely on the first day, respondent R stated a pain score of 7 to 0 on the third day. Respondent A said a pain score of 6 on the first day to 0 on the third day. Respondent B stated a pain score of 8 on the first day and became 0 on the third day. Seeing the existing results, the application of classical music therapy and finger holding was successful in reducing the intensity of pain in post-operative pain clients.